Skin aging & cancer: Ambient UV-R exposure - Dwivedi A.; Agarwal N.; Ray L.; Tripathi A.K. (My University, 2025)
This book summarizes the potent effect of ultraviolet radiation (UVR) on the photoaging and cancer formation. Skin is the largest human organ which continually reconstructs itself to ensure its viability, integrity, and ability to provide protection for the body. This protection can be compromised by the aging of the skin which ultimately promotes skin inflammation, impaired wound repair, and increased risk of skin cancer. The book entails mechanistic insights into the UVR-induced immunomodulation and DNA damage in the skin to delineate the pathogenesis, and develop novel ways for prevention of photoaging of the skin cells. It also elucidates the potential of nanotechnology in the treatment of skin cancer. Further, it discusses the bioinformatics approaches to understand the molecular mechanism of photoaging and cancer formation. © Springer Nature Singapore Pte Ltd. 2019.